Hubungan Sosial Budaya dan Pengetahuan Terhadap Minat Ibu dalam Penggunaan Alat Kontrasepsi Jangka Panjang (MKJP) di Wilayah Kerja UPTD Puskesmas Singkil Tahun 2024 - Kismiasih Adethia; Annisa Silvia; Retno Wahyuni; Diah Pitaloka; Sonia Novita Sari; Yasrida Nadeak (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
The Long-Term Contraceptive Method (MKJP) is a contraceptive that can be used for a long period of time, more than two years, effectively and efficiently for the purpose of spacing births for more than three years or terminating pregnancies in PUS who no longer want to have more children. Family planning devices/drugs/methods that include MKJP are IUD/IUD, Implant, MOP and MOW. In Aceh Province, especially Aceh Singkil, the number of couples of childbearing age (PUS) is 17,625 pairs. The most widely used contraceptive method is PIL contraception, while 216 (1.2%) use MKJP IUD contraception and 481 (2.7%) use implant contraception. The aim of this research is to analyze the socio-cultural relationship and knowledge towards mothers' interest in using long-acting contraceptives (MKJP) in the Singkil Community Health Center UPTD Work Area in 2024. This research is quantitative with a cross-sectional research design conducted in the Singkil Community Health Center UPTD Work Area. . The population in this study was 46 women of childbearing age. The sampling technique used is Total Sampling. The instrument used was a questionnaire and bivariate analysis using the Chi Square test. In conclusion, the p-value was obtained: 0.00<0.05, which means there is a socio-cultural and knowledge relationship with mothers' interest in using long-term contraceptive devices (MKJP) in the Singkil Community Health Center UPTD Work Area in 2024.